Przywołania i deskrypcje ruin w dzienniku podróży Walerii Tarnowskiej do Italii - Mazurkowa Bożena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The main part of this study is preceded by information on the subject of dynamically increasing, since the beginning of the 18th century, participation of Polish women from wealthy houses in social life. It can be confirmed by, among others, their travels abroad to e.g. Italy with its rich resources in the form of works of art including those preserved from ancient times being of great interest then. In the main stream of investigation the author focuses on the preserved French travel journal (“Mes voyages”) of the journey that Waleria from the Stroynowskis Tarnowska undertook to Italy in years 1803–1804 with her husband Jan Feliks and her father Walerian. The analytical and interpretational considerations refer to the fragments concerning the buildings observed by the countess during her Italian journey, which were to a various degree damaged by the power of time or human activity and that was indicated by singled out synonymous terms used for ruins. The crucial aspect of this reflection is concretisation of Tarnowska’s impressions depicted in descriptions from close contact with antique and modern edifices, not too rarely preserved in a remnant form. According to the author of this study references to and descriptions of ruins in the analysed journal are the expression of not a genuine passion but rather of the influence of contemporary fashion for ancient times and great curiosity for the world during the first journey abroad and the will to see and then record in writing all that was required to see during this Italian trip. They also prove psychologically conditioned perception of wors of art.
References to and Descriptions of Ruins in the Travel Journal by Waleria Tarnowska to Italy
Keywords: Waleria Tarnowska; travel journalling; ruins; enlightenment; Italy; podróżopisarstwo; ruiny; Oświecenie; Italia